Estudo da malha urbana e proposta de implantação de um parque tecnológico na cidade de Jacareí - Pires, Geison da Veiga [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
The city of Jacareí above average presents a economic growth of the State of São Paulo, fact that comes if reflecting in the quality of life of the citizens, due to lack of infrastructure to hold the growth rhythm. Today the commercial center of the city, presents diverse urban conflicts with its narrow streets and sidewalk making it difficult to the locomotion and the access the areas and building of public interest gifts in this region. Aiming at the arrival of four multinationals that already make gratings investments in the city and the promise of growth and dinamização of the still bigger economy for the next years, this work studies the urban mesh of the city for a possible implantation of a Technological Park that serves of inductive element of the development of the region north of the city of Jacareí. Place, in which, they are being constructed the multinationals and where, according to Managing Plan of the city, the city hall intends to urbanizar in the next years, with the objective to minimize the areas of urban conflict in the commercial center and of form to absorb the growth of the city. From the study of old experiences, of works carried through on the subject, interviews with city planners of the e region after visits to the place, we will go to argue the possibility of implantation of the Technological Park in Jacareí and optimum place for its installation

A cidade de Jacareí vem apresentando nos últimos anos um crescimento econômico acima da média do Estado de São Paulo, fato que esta refletindo na qualidade de vida dos cidadãos, devido à falta de infraestrutura para comportar o ritmo de crescimento. Hoje o centro comercial da cidade, apresenta diversos conflitos urbanos com suas ruas e calçadas estreitas dificultando à locomoção e o acesso as áreas e prédios de interesse público presentes nessa região. Visando a chegada de quatro multinacionais que já fazem grandes investimentos na cidade e a promessa de crescimento e dinamização da economia ainda maior para os próximos anos, esse trabalho estuda a malha urbana da cidade para uma possível implantação de um Parque Tecnológico que sirva de elemento indutor do desenvolvimento da região norte da cidade de Jacareí. Local, no qual, estão sendo construídas as multinacionais e onde, segundo o Plano Diretor do município, a prefeitura pretende urbanizar nos próximos anos, com o objetivo de minimizar as áreas de conflito urbano no centro comercial e de forma a absorver o crescimento da cidade. A partir do estudo de experiências antigas, de trabalhos realizados sobre o assunto, de entrevistas com urbanistas da região e após visitas ao local, iremos discutir a possibilidade de implantação do Parque Tecnológico em Jacareí e o melhor lugar para sua instalação
Keywords: Planejamento urbano - Jacareí; Desenvolvimento integrado; Urbanização; Technological Park - Requirements for implementation